ONE OF THE REASONS OF GAS PERFORMANCE IN THE WELLS OF UZBEKISTAN DEPOSITS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the reasons for the occurrence of gas shows during tripping operations and exceeding the critical drilling speed in the productive formation. A formula is given for limiting the rate of penetration in a gas-saturated reservoir in order to prevent gas production and its subsequent transition to an open gas fountain.